Can off-field `brains` provide a competitive advantage in professional football? - McCall, A.; Davison, M.; Carling, C.; Buckthorpe, M.; Coutts, A. J.; Dupont, G. (British Journal of Sports Medicine, 2016)
`Working-fast and working-slow` in sport describes the concept that practice and research can be integrated to improve high-performance outcomes and enhance professional practice. `Working-fast` is the task of the fast-thinking, intuitive practitioner operating on `the ground` at a frenetic pace, interacting with coaches and athletes, and delivering the daily preparation programme. `Working-slow` is key for the team's deliberate, focused researcher acting as the resident sceptic, operating behind the scenes on tasks that the `fast-practitioner` may not have time and/or skills to undertake. Such hidden, but important, tasks include determining measurement noise/error in performance tests, establishing proof of concept for new ideas and ensuring validity of methods. Embedding research into the fast environment of high-performance football may provide a competitive advantage using ethical and evidence-based methods.